Assistance of metagenomics next-generation sequencing for diagnosis of adenovirus pericarditis with pericardial effusion in a child: a case report and literature review - Lin, Liangkang; Xu, Min; Zhang, Haiyang (Frontiers in Pediatrics, 2023)
Human adenoviruses can cause infection at any age, but are most common in the pediatric population, especially young children and infants, with a peak incidence in infants and children from 6 months to 5 years of age. Adenovirus infection can cause severe pneumonia, but pericarditis from adenovirus infection was very rare. This article reports a case of a 2-year-old patient with pericarditis caused by adenovirus infection and a moderate pericardial effusion. We detected positive adenovirus nucleic acid in the blood by polymerase chain reaction(PCR) assay.And human adenoviruses was identified by metagenomics next-generation sequencing (mNGS) in blood and pericardial effusion. According to the test results and clinical practice, active symptomatic and supportive treatment was given, and finally the child recovered and was discharged from the hospital. Comprehensive and accurate diagnosis of pathogens is a prerequisite for effective treatment, and mNGS provides an effective means for diagnosing rare adenovirus myocarditis in children.